Neuroanatomy and Neurophysiology of the Corrupt-Prone Brain: Where Morality, Cognition, and Behaviour Intersect - Abdullah, Jafri Malin; Mat Saat, Geshina Ayu; Mustafar, Faiz; Lebai Lutfi, Syaheerah (Malaysian Journal of Medical Sciences, 2026)
In Malaysia, corruption analyses and brain, and mind and neuroscience; are two critical domains of enquiry that seek to advance research that bridges medicine, clinical neurophysiology and neurotechnology by 2050. Local universities, both public and private, must initiate studies into how corruption and malpractice—and their resulting economic losses to the nation—can be prevented. An understanding of neuroanatomy, neurophysiology. and neurochemistry will hopefully advance knowledge of how the human brain can be trained to resist corruption and, eventually, be rehabilitated